1993
DOI: 10.1177/140349489302100308
|View full text |Cite
|
Sign up to set email alerts
|

Modernization and Smoking — Regional Differences in Adolescent Smoking in Finland in 1977–1987

Abstract: The purpose of the study was to test the applicability of the modernization framework to changes and regional diversity in adolescent smoking. A biannual cross-sectional survey data from the Adolescent Health and Lifestyle Survey was used. A national sample of 14, 16- and 18-year-old Finns answered a mailed questionnaire every other year from 1977. The 1977, 1979 and 1981 data were pooled as were data from 1983 and 1985 (N = 8505, 9777). The 1987 sample was weighted in accordance with the province size (N = 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…These are consistent with research findings documented in other countries, for example, Finland, 8-11 the United States, 14 and Bavaria. 12 Various reasons have been attributed to these difference,s including social norms, 11 family status and relationships, 11 level of modernization and urbanization, 8 education and socioeconomic status, 12 religious beliefs, 9 political and other ideologies, 12 and so on. In exploring the underlying mechanisms for the effects of regional contexts on health behaviors, researchers have put forward various conceptual frameworks.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These are consistent with research findings documented in other countries, for example, Finland, 8-11 the United States, 14 and Bavaria. 12 Various reasons have been attributed to these difference,s including social norms, 11 family status and relationships, 11 level of modernization and urbanization, 8 education and socioeconomic status, 12 religious beliefs, 9 political and other ideologies, 12 and so on. In exploring the underlying mechanisms for the effects of regional contexts on health behaviors, researchers have put forward various conceptual frameworks.…”
Section: Discussionsupporting
confidence: 92%
“…A series of studies conducted in Finland in the 1990s revealed significant variations in health behaviors. 8-11 The study by Karvonen et al 8 found that modernization played an important role in regional differences in adolescent smoking. Torsten et al 9 documented the influence of religiousness on the regional differences in alcohol drinking.…”
Section: Introductionmentioning
confidence: 99%
“…The research evidence (Rimpela et al 1991, Pulkkinen & Tremblay 1992 indicates that unhealthy life habits are an integral part of problem behaviour. It has also been shown (Sajiwandani 1991, Karvonen et al 1993, Pulkkinen 1993) that the development of a life style is a holistic process which is connected with the adoles-cent's growth and development. It is essential that the young person should cope with all the developmental tasks he or she is faced with.…”
Section: Discussion and Conclusiommentioning
confidence: 99%